Evaluation of Growth and Yield of Indian Oyster Mushroom Pleurotus pulmonarius (Fr.) Quél. on Three Agricultural Wastes Supplemented with Cottonseed Hulls (CSH) in Uganda - Serunjogi, Stephen K.; Rwakaikara-Silver, Mary; Nakavuma, Jessica; Isikhuemhen, Omoanghe S. (International Journal of Medicinal Mushrooms, 2005)
The main economic activity in Uganda is agriculture, which provides livelihood for over 80% of the country’s population. However, the ever rising population on static land resources has led to decline in agricultural productivity. Consequently, there is a decline in household incomes, thus compromising government eff orts to fi ght poverty and food insecurity. To avert this scenario, Ugandan farmers and the Ugandan Government are keen to explore and develop alternative livelihood strategies. Mushroom cultivation offers a viable solution because currently there is a strong demand for mushrooms, locally and internationally. In order to sustain production to meet this demand, improvement of cultivation practices is paramount. Locally, cottonseed hulls (CSH) is the major substrate commonly used for cultivation, especially in urban areas, where most farmers are located. Supply of this substrate is limited as a result of decline in cotton productivity. There is scarcity of the substrate (CSH) mainly because of its multipurpose use in agricultural communities coupled with high costs of transportation from the remote cotton producing areas. Therefore, it became necessary to evaluate other alternative abundant substrates in whole or in combination with CSH in mushroom production.
Keywords: livelihood; agriculture; mushroom